A Novel Clustering Algorithm Inspired by Membrane Computing. (22nd March 2015) - Peng, Hong; Luo, Xiaohui; Gao, Zhisheng; Wang, Jun; Pei, Zheng
Abstract : P systems are a class of distributed parallel computing models; this paper presents a novel clustering algorithm, which is inspired from mechanism of a tissue-like P system with a loop structure of cells, called membrane clustering algorithm. The objects of the cells express the candidate centers of clusters and are evolved by the evolution rules. Based on the loop membrane structure, the communication rules realize a local neighborhood topology, which helps the coevolution of the objects and improves the diversity of objects in the system. The tissue-like P system can effectively search for the optimal partitioning with the help of its parallel computing advantage. The proposed clustering algorithm is evaluated on four artificial data sets and six real-life data sets. Experimental results show that the proposed clustering algorithm is superior or competitive to k -means algorithm and several evolutionary clustering algorithms recently reported in the literature.